2019
DOI: 10.1055/s-0039-3400227
|View full text |Cite
|
Sign up to set email alerts
|

17-OHPC to Prevent Recurrent Preterm Birth in Singleton Gestations (PROLONG Study): A Multicenter, International, Randomized Double-Blind Trial

Abstract: Background Women with a history of spontaneous preterm birth (SPTB) are at a significantly increased risk for recurrent preterm birth (PTB). To date, only one large U.S. clinical trial comparing 17-OHPC (17-α-hydroxyprogesterone caproate or “17P”) to placebo has been published, and this trial was stopped early due to a large treatment benefit. Objective This study aimed to assess whether 17-OHPC decreases recurrent PTB and neonatal morbidity in women with a prior SPTB in a singleton gestation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
172
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(189 citation statements)
references
References 15 publications
3
172
1
4
Order By: Relevance
“…There was relatively low (23%) enrollment in the US because 17P was considered standard of care in the US; as such, investigators were reluctant to randomize patients to a placebo-controlled trial. Thus, the PROLONG trial population was predominantly (77%) outside of the US, in countries with markedly lower background rates of PTB [10]. In contrast to the Meis trial, the PROLONG trial did not demonstrate a significant reduction in PTB with 17P; the incidence of PTB at <35 weeks was 11.0% in the 17P group vs 11.5% in the placebo groups.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…There was relatively low (23%) enrollment in the US because 17P was considered standard of care in the US; as such, investigators were reluctant to randomize patients to a placebo-controlled trial. Thus, the PROLONG trial population was predominantly (77%) outside of the US, in countries with markedly lower background rates of PTB [10]. In contrast to the Meis trial, the PROLONG trial did not demonstrate a significant reduction in PTB with 17P; the incidence of PTB at <35 weeks was 11.0% in the 17P group vs 11.5% in the placebo groups.…”
Section: Introductionmentioning
confidence: 87%
“…PROLONG was an international, multi-center, randomized, double-blind, placebo-controlled trial conducted by a pharmaceutical sponsor, with enrollment between 2009 and 2018 [10]. PROLONG was designed in conjunction with the FDA as a required confirmatory trial.…”
Section: Prolongmentioning
confidence: 99%
See 2 more Smart Citations
“…30,38 A double-blind, placebo-controlled, international (PROLONG) trial published in 2019 found no benefit of weekly IM injection of 250 mg of 17-OHPC (from 16 to 36 weeks of gestation) compared to placebo in decreasing recurrent PTB risk and neonatal morbidity when given to women with singleton gestation and a history of SPTB. 39…”
Section: What Is the Role Of Progesterone In Singleton Pregnancies Wimentioning
confidence: 99%